Ethnobotanical Wealth of Jandool Valley, Dir Lower, Khyber Pakhtunkhwa (Kpk), Pakistan - Nasrullah; Mohammad Nisar; Suliman; Zahid Ali (International Journal of Phytomedicine, 2012)
The present study contributes to enlist the wealth of ethnobotanical important plants of Jandool valley, Dir lower, Khyber Pakhtunkhwa (KPK), Pakistan. A total of 67 plants species, belonging to 39 families of herbs (57 %), shrubs (6 %), trees (34 %) and mushrooms (3 %) were found to be used by the local inhabitants generally for medicinal, timber wood, fuel, food and fodder purposes. Majority of the plants identified were used for more than one purpose. The human and cattle pressure has resulted in loss of the indigenous ethnobotanical important plant species. Therefore reforestation followed by proper protection is a need of time.